Covariance data evaluation for 233U. (March 2018) - Alrwashdeh, Mohammad
Abstract: The FITWR program was developed and applied to experimental nuclear data by using the weighted least square method with nonlinear regression for high-order polynomials to meet the growing demands of nuclear data. It can deal with provided variance and covariance data along with experimental data to obtain evaluation data. The aim of this study was to investigate the validity and accuracy of the cross-sectional data for 233 U to perform the calculations of the critical system by performing the pre-calculations using the SAMMY code as follows. First, by using the Bayes method, which is available in the SAMMY code, and then by using the FITWR code, which consists of facilitated weighted least square method with nonlinear regression. To validate the FITWR fitting method, a comparison was made with the Bayes method for several benchmarks, and it was tested in both thermal and fast-energy regions. All the computational work done for this paper was carried out at IMAN1 Center – Jordan's National Supercomputing Center.